Dad as a Coach: Fatherhood and Voluntary Work in Youth Sports - Magnus Kilger (MDPI AG, 2020)
One central issue in sports is the role of informal learning in organized child and youth sport in contrast to learning in the school context of physical education (PE). In Scandinavia, the model for organizing sports include an independent sports organization that organizes child and youth training on many levels, including the grassroots level and elite competitions organized within non-profit clubs and based on non-salaried voluntary work. In contrast to the public schooling context where physical education is led by educated and professional PE-teachers, organized child and youth club sports are based on parental engagement. Drawing on ten interviews with male coaches training their own children, this study examines how fathers are handling learning in the dual position as a father and a coach. This narrative analysis focuses on the theoretical concept of dilemmatic spaces in interviews and shows how shared cultural and societal storylines are used by the parental coaches in their personal stories. The results illustrate three dilemmatic spaces of learning that the participants must rhetorically handle. The first dilemma illuminates the dual position of both being a father, and at the same time acting as a coach. In the second dilemma, the fathers are seeking to balance between care of their child and increasing performance development. The third dilemma is balancing the training as child/parent quality time and the need for children to develop autonomy. The results show how the dual position of being a father and a coach can be both an asset in the relational building but also highly problematic and, in any case, involves a relational identity change. Learning in this dual position means that the fathers cannot act entirely as a coaches and disregard or override their parental position.